(untitled) (Panacea Journal of Medical Sciences, 2025)
Background: To evaluate the danger of transmission of pathogenic organisms via the white coats of medical students in college. It is important to determine the degree and kind of microbial contamination that was present on white coats. This study also looked into how the students handled and cleaned their coats as well as what were their perceptions about contamination through white coats. Materials and Methods: This was a cross-sectional study carried out at the NCRIMS, Meerut from August 2022 to September 2022. 176 white coats worn by medical students in total were sampled for potential contamination by bacteria. Result: 67.04% of the 176 white coats that were screened were found to be contaminated. Major contaminants were Gram-positive bacteria (89.83% of the contaminated coats) while only 10.16% were Gram-negative bacteria. The perception of medical students towards the spread of nosocomial infections through white coats was also studied which reflected a poor hygienic practice regarding their white coats. Conclusion: The following recommendations may be made on the basis of this study. First, it should become mandatory to purchase white coats on an annual basis and to always have two or more on hand. Whitecoat wearers should be urged to wash their white coats on a weekly basis. This study offers microbiological proof in favour of barring white coats from non-clinical areas of the hospital.